Implikasi Psikologis Beban Kenabian (Prophetic Burden): Sebuah Eksegesis Naratif Kehidupan Musa Dalam Bilangan 11:11-15 - Avlorina, Mey (Sekolah Tinggi Teologi Injili Indonesia Palu, 2026)
This study examines the psychological dynamics of Moses’ leadership during the wilderness crisis through a narrative exegetical analysis of Numbers 11:11–15. Unlike previous studies that emphasize historical and theological-political aspects, this research highlights the concept of prophetic burden as a form of mental strain involving emotional exhaustion, cognitive distortion, and deep despair. Using a narrative-critical approach, the analysis shows that Moses’ distress is driven by excessive internalization of responsibility and social isolation, shaping his theological perception of God. The narrative resolution, through the appointment of seventy elders, demonstrates that leadership burdens are not meant to be borne individually. The study concludes that Scripture acknowledges the emotional vulnerability of leaders and affirms the necessity of a collective model of leadership in addressing ministry burnout.